Effects of artificial feeds on growth and production of fishes in Polyculture (International Journal of Agricultural Research, Innovation and Technology, 2015)
A study on the effects of artificial feeds on growth and production of fishes along with some limnological conditions were conducted in polyculture system. Species of Indian major carp (Cirrhinus mrigala) and exotic fishes (Hypophthalmicthys molitrix and Oreochromis niloticus) were stocked in six ponds under two treatments, each with three replications. Stocking rate in both treatments was 100 fish per decimal at the ratio of silver carp: tilapia: mrigal = 2: 2: 1. Fertilization and artificial feeds were given in Ttreatment 1 (T1) and only fertilization was done in Treatment 2 (T2). Wheat bran, rice bran and soybean meal were given daily as artificial feed in T1 in the ratio of wheat bran: rice bran: soybean meal = 2: 2: 1 (by wt). Urea, T.S.P and cow dung were applied fortnightly at the rate of 60 g deci-1, 90 g deci-1 and 2 kg deci-1 respectively. Water temperature, transparency, pH, dissolved oxygen, free CO2, total alkalinity, PO4-P and NO3-N were determined fortnightly and phytoplankton and zooplankton were studied fortnightly. These limnological conditions were more or less similar in the ponds under two treatments and were within suitable ranges. Calculated gross and net yields of fish were 16.56 and 12.48 ton ha-1 respectively in case of fertilization and artificial feeding application (T1) and 9.99 and 5.91 ton ha-1 respectively in case of only fertilization (T2). Application of artificial feed in T1 significantly increased the growth and production of fish more than two times which indicates that artificial feeding in polyculture is very useful for increasing fish production. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22637 Int. J. Agril. Res. Innov. & Tech. 4 (2): 11-15, December, 2014